Ingredients in Commercially Available Mouthwashes - Oktay Yazicioglu; Musa Kazim Ucuncu; Kerem Guven (Elsevier, 2024)
ABSTRACT: Objectives: Mouthwashes, a cornerstone of oral and dental hygiene, play a pivotal role in combating the formation of dental plaque, a leading cause of periodontal disease and dental caries. This study aimed to review the composition of mouthwashes found on retail shelves in Turkey and evaluate their prevalence and side effects, if any. Methods: The mouthwashes examined were sourced from the 5 largest chain stores in each district of Istanbul. A comprehensive list of the constituents was meticulously recorded. The research was supported by an extensive compilation of references from scholarly databases such as Google Scholar, PubMed, and ScienceDirect. Through rigorous analysis, the relative proportions of mouthwash ingredients and components were determined. Results: A total of 45 distinctive variations of mouthwashes, representing 17 prominent brands, were identified. Amongst the 116 ingredients discovered, 70 were evaluated for potential adverse effects and undesirable side effects. The aroma of the mouthwash (n = 45; 100%), as welll as their sodium fluoride (n = 28; 62.22%), sodium saccharin (n = 29; 64.44%), sorbitol (n = 21; 46.6%), and propylene glycol (n = 28; 62.22%) content were the main undesireable features. Conclusions: The limited array of mouthwashes found on store shelves poses a concern for both oral and public health. Furthermore, the intricate composition of these products, consisting of numerous ingredients with the potential for adverse effects, warrants serious attention. Both clinicians and patients should acknowledge the importance and unwarranted side effects of the compnents of the mouthwashes.